Physicochemical properties changes on woody biomass torrefaction : effect of temperature and residence time - Yeo, Boon Kiat (2017)
Biomass can be used as a source of energy and it most often refers to plants or plant-based materials such as woody sawdust or oil palm residues. Wood waste was the one important biomass energy source to convert to value added product which was carbon particles. The best option to overcome the issues face with biomass was to carry out a pre-treatment process called torrefaction. Torrefaction is a pre-thermal treatment that has the potential to improve these characteristics. This thesis covers three areas of investigation work. The first area investigated the influence of fundamental parameters (temperature, residence time) on the behaviour of woody biomass when treated with torrefaction. The woody biomass used in this study were Meranti and Seraya, had been torrefied in furnace at temperatures of 240 oC, 270 oC, 300 oC and 330 oC with inert nitrogen gas for the residence time 30 min and 60min. As a whole, the torrefaction temperature was increased, the mass of the torrefied wood was decreased. Moreover, higher the torrefaction temperature caused the energy loss decreased in shorter duration. The second area that covered how torrefaction has improved the physical and chemical properties of biomass. Torrefied fuels contained higher energy yields behaviours between both sawdust used which were Meranti and Seraya sawdust. Furthermore, SEM studies were carried out to gain a better insight into any changes in morphology and chemical composition of torrefied biomass. The overall results indicated that careful optimization was required to maximize the benefits of torrefaction whilst maintaining a good energy yield. The third area examined the nature of products of torrefaction in terms of composition, proximate and ultimate analysis to provide comparisons between the products obtained from torrefaction and when the woody biomass were untreated. The presence of mass and heat transfer limitations was suggested to explain the observed significant changes.